Perilaku Caring Perawat Berdasarkan Teori Jean Watson di Ruang Rawat Inap - Cecep Solehudin Firmansyah; Richa Noprianty; Indra Karana (Jurnal Kesehatan Vokasional, 2019)
Background: Caring is a nurse's concern to clients was form of attention, appreciation and able was meet their needs. Phenomenon who had four out of five clients interviewed mentioned nurses less caring for clients. Objective: Less caring her nurses marked with less caring nurses to clients, so clients complain that the nurses in the room less attention to the convenience of clients.Methods: The type was of quantitative research with descriptive survey approach. The sample used was inpatient minimum patient duration of 3 days with total sampling technique was is 142 people. Data collection of primary data with research instrument that is questionnaire Behaviors Assessment Caring was of ten carative factor Jean Watson. Data analysis is frequency distribution.Results: Result of research on caring behavior of nurse 52,1% that was enough, fulfillment of human need 73,2%, Altruistic Humanistic Value System 43,7%, Confidence and expectation of client 47,9%, Sensitivity to self and others 50,0% , Relationship helps confidence 48,6%, recipient of positive and negative expression 51,4%, Problem solving method 47,2%, Interpersonal teaching process 45,1%, Psychological environment 60,6% sufficient nurse caring behavior and phenomenological existential power client assess 44,4% caring behavior of nurse that is good.Conclusion: It is concluded that the client assess the caring behavior of the nurses have enough category, therefore therefore for the hospital can evaluate about caring conducted by nurses in RSAU DR. M. Salamun Bandung.